Diverse migratory portfolios drive inter‐annual switching behavior of elk across the Greater Yellowstone Ecosystem - Gabriel R. Zuckerman; Kristin J. Barker; Laura C. Gigliotti; Eric K. Cole; Justin A. Gude; Mark A. Hurley; Matthew J. Kauffman; Daryl Lutz; Daniel R. MacNulty; Eric J. Maichak; Doug McWhirter; Tony W. Mong; et al. (Ecosphere, 2023)
Abstract A growing body of evidence shows that some ungulates alternate between migratory and nonmigratory behaviors over time. Yet it remains unclear whether such short‐term behavioral changes can help explain reported declines in ungulate migration worldwide, as opposed to long‐term demographic changes. Furthermore, advances in tracking technology reveal that a simple distinction between migration and nonmigration may not sufficiently describe all individual behaviors. To better understand the dynamics and drivers of ungulate switching behavior, we investigated 14 years of movement data from 361 elk in 20 herds across the Greater Yellowstone Ecosystem (GYE). First, we categorized yearly individual behaviors using a clustering algorithm that identified similar migratory tactics across a continuum of behaviors. Then, we tested seven hypotheses to explain why some ungulates switch behaviors, and we evaluated how behavioral changes affected the proportions of different behaviors across the system. We identified four distinct behavioral tactics: residents (4.8% of elk‐years), short‐distance migrants (53.7%), elevational migrants (21.9%) and long‐distance migrants (19.6%). Of the 20 herds, 18 were partially migratory, and 5 had all four movement tactics present. We observed switches between migratory tactics in all sets of consecutive years during our study period, with an average of 22.5% of individual elk changing movement tactics from one year to the next. Elk in herds with higher movement tactic diversity were significantly more likely to switch tactics and often responded more effectively to adverse environmental conditions, compared to those in herds with low movement tactic diversity. During our study period, switching increased the prevalence of both short‐ and long‐distance migrants, decreased the prevalence of elevational migrants, and had no effect on the prevalence of residents. Our findings suggest that rather than contributing to the declining migratory behavior found in the GYE, switching behavior may enable greater resiliency to continuously changing environmental and anthropogenic conditions.